Computer science to the Point Computer Science for Life Sciences Students and Other Non-Computer Scientists - Tolg, Boris (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2023)
This textbook is aimed at students of non-specialist courses with computer science components. Special emphasis is placed on the so-called life sciences, such as medical technology, rescue engineering, biotechnology, environmental engineering or process engineering. The textbook is suitable for readers in study and practice who want to get an introduction to computer science. The special feature of this book is the problem-based approach, as well as the exercises designed according to different taxonomy levels. The contents Introduction to computer science Basics of programming in C++ Arrays and pointers File operations Object orientation and inheritance The author Prof. Dr.-Ing. Boris Tolg teaches computer science, mathematics and simulation in medicine and heads the SIMLab laboratory in the Department of Medical Technology at HAW Hamburg. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Introduction to computer science -- Basics of programming in C++ -- Arrays and pointers -- File operations -- Object orientation and inheritance.
Keywords: Engineering mathematics; Engineering -- Data processing; Bioinformatics; Social sciences -- Data processing; Mathematical and Computational Engineering Applications; Computational and Systems Biology; Computer Application in Social and Behavioral Sciences